2020
DOI: 10.3390/app10165407
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between Surface Properties and Snow Adhesion and Its Shedding Mechanisms

Abstract: Understanding the mechanisms of snow adhesion to surfaces and its subsequent shedding provides means to search for active and passive methods to mitigate the issues caused by snow accumulation on surfaces. Here, a novel setup is presented to measure the adhesion strength of snow to various surfaces without altering its properties (i.e., liquid water content (LWC) and/or density) during the measurements and to study snow shedding mechanisms. In this setup, a sensor is utilized to ensure constant temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…45 Similar phenomenon was also reported in Sojoudi et al's work, in which they suggested that extreme rough surfaces would lead to small contact area between snow and surface, resulting in low snow adhesion strength. 46 Effects of Quartz Sand. Sand production is a large issue for unconsolidated sandstone reservoirs, especially for natural gas hydrate reservoirs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…45 Similar phenomenon was also reported in Sojoudi et al's work, in which they suggested that extreme rough surfaces would lead to small contact area between snow and surface, resulting in low snow adhesion strength. 46 Effects of Quartz Sand. Sand production is a large issue for unconsolidated sandstone reservoirs, especially for natural gas hydrate reservoirs.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In fact, the adhesions of numerous solid precipitations (e.g., ice, snow, and scale) are the function of substrates surface property. 34,46,48 Recently, Sojoudi et al and Smith et al reported a strong linear relationship between the adhesion strength of the THF/CyC5 hydrate and the practical work of adhesion between a droplet and the underlying substrate. 20,49 Herein, the measured sintered hydrate deposit adhesion strength under different conditions, τ h , versus the calculated work of adhesion for a droplet was plotted in Figure 7(a).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Note that Γ and τtrue^ values are likely to be different between snow and ice, due to the difference in the physical/mechanical properties between them. [ 4 ] For example, the modulus of snow can vary from ≈100 kPa to 8 GPa (that of bulk ice).…”
Section: Fabrication and Testing Of Coatings For Ice And Snow Sheddingmentioning
confidence: 99%
“…Here, snow was generated using a snow gun operating inside a walk-in cold room that could reach temperatures up to − 20 °C [41]. Water and compressed air Fig.…”
Section: Snow Formation and Characterizationmentioning
confidence: 99%
“…The LWC of snow grains is an important parameter that affects the interfacial forces during the impact. It has been proved that snow has its maximum cohesion and adhesion strengths at LWC values of ≈ 20%, and consequently stick strongly to surfaces [40,41]. Due to weak stickiness of dry snow grains (LWC < 5%) to surfaces, snow accumulation at sub-freezing temperatures is limited to low wind velocities [27].…”
Section: Introductionmentioning
confidence: 99%